2016
DOI: 10.1016/j.actbio.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

High content analysis platform for optimization of lipid mediated CRISPR-Cas9 delivery strategies in human cells

Abstract: Non-viral gene-editing of human cells using the CRISPR-Cas9 system requires optimized delivery of multiple components. Both the Cas9 endonuclease and a single guide RNA, that defines the genomic target, need to be present and co-localized within the nucleus for efficient gene-editing to occur. This work describes a new high-throughput screening platform for the optimization of CRISPR-Cas9 delivery strategies. By exploiting high content image analysis and microcontact printed plates, multi-parametric gene-editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
0
23
0
2
Order By: Relevance
“…Techniques such as micropatterning, that segregate populations into unique units, lend themselves well to high content imaging, analysis and screening [69] which enables facile assaying of phenotype and the selection of homogenous subpopulations. Previous studies demonstrated the utility of this in situ monitoring approach in evaluating heterogeneity in CRISPR-Cas9 delivery strategies [70] and editing of pluripotent stem cells [71]. Taken together, this body of work illustrates how biomaterials can provide a powerful platform for the guidance, monitoring, analysis, and quality control of cell populations.…”
Section: Roles For Engineered Biomaterialsmentioning
confidence: 81%
See 1 more Smart Citation
“…Techniques such as micropatterning, that segregate populations into unique units, lend themselves well to high content imaging, analysis and screening [69] which enables facile assaying of phenotype and the selection of homogenous subpopulations. Previous studies demonstrated the utility of this in situ monitoring approach in evaluating heterogeneity in CRISPR-Cas9 delivery strategies [70] and editing of pluripotent stem cells [71]. Taken together, this body of work illustrates how biomaterials can provide a powerful platform for the guidance, monitoring, analysis, and quality control of cell populations.…”
Section: Roles For Engineered Biomaterialsmentioning
confidence: 81%
“…This can be done using multivariate design of experiments (DOE) approaches to systematically examine the significance and interactions of process parameters, while reducing sample size and effort required compared to conventional methods. For example, integrating biomaterials with DOE methods allow efficient optimization of biomaterial properties for factor delivery[70] or cell functionality[86]. Altogether, biomaterials are suitable as standardized reference materials that could be used as benchmarks in the biomanufacturing process.…”
Section: Roles For Engineered Biomaterialsmentioning
confidence: 99%
“…Bunlarla birlikte ticari olarak bulunan transfeksiyon kitleri de değişen oranlardaki verimlilikle CRISPR-Cas9 sisteminin taşınmasında kullanılmıştır. 59 Non-viral gen aktarımı yöntemleri arasında, fiziksel yöntemler olarak bilinen yön-temler de CRISPR-Cas9 sisteminin hücrelere aktarılmasında kullanılabilir. Bunlar arasında elektroporasyon, mikroinjeksiyon ve hidrodinamik injeksiyon bulunmaktadır.…”
Section: Crispr-cas9 Si̇stemi̇ni̇n Transfeksi̇yon Ve Taşinma Strateji̇leri̇unclassified
“…51,60,61 Genel olarak viral ve viral olmayan vektörler karşılaştırılacak olursa Tablo 2'deki gibi bir durum ortaya çıkmaktadır. 44,59,62,63 Buna göre viral vektör-ler yüksek verimle CRISPR-Cas9 sisteminin taşın-masında kullanılma potansiyeline sahiptir. Ancak bunun yanında mutajenite ve immunojenite riski taşımalarından dolayı viral olmayan transfeksiyon ve gen taşıma yöntemlerinin önemi ortaya çık-maktadır.…”
Section: Crispr-cas9 Si̇stemi̇ni̇n Transfeksi̇yon Ve Taşinma Strateji̇leri̇unclassified
“…This system is able to create both germ line and somatic animal models with point mutations, deletions and complex chromosomal rearrangements and thus could be directly applied to pain related 49 . Microfluidic membrane deformation method to deliver sgRNA and Cas9 into various cell types such as hard to transfect lymphoma cells and embryonic stem cells while maintaining high cell viability have been developed and have demonstrated to be highly efficient in genome editing and successful in generation of gene-knockout cell lines.…”
Section: Cas9 In Cancer Research Diagnosis and Therapeuticsmentioning
confidence: 99%